DYNAMICS OF RUSSIAN-KYRGYZ RELATIONS: FROM THE CENTER-PERIPHERY TO UNILATERAL DEPENDENCE? - HORÁK, Slavomír (CENTRAL ASIA AND THE CAUCASUS, 2007)
By Central Asian standards, Kyrgyzstan is a relatively small country. Its natural riches are limited to gold and water resources; other than that it has nothing to offer on the global and regional scale, which explains its insignificant geopolitical weight. Tucked away in a corner of the region, it is isolated from the main routes of Asian freight turnover and its mountains make transit unprofitable (especially compared with its neighbors). It cannot deal on an equal footing with its large neighbors—Kazakhstan, China, and Uzbekistan; potential investors prefer to keep away from the region with its unstable or potentially unstable countries, such as Afghanistan and Uzbekistan. The image of a backward country, from which its citizens are leaving in hundreds of thousands to seek employment elsewhere and which is short of skilled workers, does nothing to attract money to the Kyrgyz economy. Its economic environment—closed to foreign investors and non-transparent because of corruption and clientelism—can hardly tempt real money. The country’s geopolitical situation is highly disadvantageous, partly because of outside factors on which the Kyrgyz elite, no matter what shape it is in, has no influence. The country is an obvious regional, Eurasian, and even Asian periphery.1 However, in keeping with Mackinder’s theory of the Heartland as applied to Central Asia,2 people are apt to believe that the country’s situation is not hopeless. This looks like an exercise in wishful thinking. I have undertaken here to explain how the Kyrgyz leaders tried to respond to the geopolitical developments and to trace the dynamics of the relations with the former Center, very much affected by a certain amount of latent momentum in their bilateral relations. The larger part of the local elite regards Russia as a center of gravity that could and should be consulted. Seen from Moscow, the Kyrgyz capital looks like the center of a former Soviet republic, that is, on the periphery of its sphere of influence to be treated, because of its obvious weakness, with a certain amount of condescension. This approach shaped a certain type of relations and contributed, albeit indirectly, to certain obstacles and problems.